Analysis of the Efficiency of Maternal and Child Health Services (MCH) at Public Health Centers in the Banyumas District (Association of Public Health Scholars based in Faculty of Public Health, Sriwijaya University, 2023)
Maternal and Child Health (MCH) service programs as an indicator of the status of community's health status are available at every Public Health Center (PHC) in Banyumas District. However, these services are still inadequate to improve the health status of mothers and children. The condition of the COVID-19 pandemic in early 2020 caused several MCH services not to run as previously planned. This study aimed to describe the implementation and efficiency of MCH services in PHC in Banyumas Regency. The method used in this study was a quantitative approach using secondary data on health workers and the output of MCH services at the PHC. Data were analyzed using the Data Envelopment Analysis (DEA) method, with the unit of analysis being aggregate data at 10 selected PHCs using a purposive sampling technique. The results showed that 60% of the PHCs were technically efficient (VRS value 1,0), and 40% of the PHCs were technically inefficient (VRS value < 1,0). The analysis's findings indicated there were differences between efficient and inefficient PHCs in terms of the input (health personnel) and output (service use). The inefficiency of the PHC is caused by the less optimal utilization of health workers and the low utilization of PHC health services by the community. Additionally, to meet the coverage of service criteria set by the government, MCH services at the PHC in the Banyumas Regency region have been provided following the current standard operating procedures. Public Health Centers must maximize the utilization of health personnel to improve technical efficiency and condition service activities during the pandemic by adjusting regional policies while still complying with health protocols.